Answer:
g(4)=f(2)
Step-by-step explanation:
f(2)=3(2)-1
f(2)=6-1
f(2)=5
We then get:
g(x)=f(2)
subsitute 5 for f(2)
g(x)=5
now solve
5=2x-3
add 3
8=2x
divide 2
4=x
so the answer is x=4 or
g(4)=f(2)
Answer:
hdhcbhxbjftfzfbhrgegdbhdvfhhdshhtjrtjrhgdhtrhhdhrhgrrggrdgfhfhgfjjythrhthrurhgrehrh
Step-by-step explanation:
vfhdbdshgrdjfhfujdrjyhzgtjybh5kitggdegrjnrrhrutjrjhtjjtdhrhhfhhrshfngnhdhgrhffhrhdhgrrhureuufdjrrjddhdhfmmghtluhfhhgkjjjjjjghifretuyferhhgeetuhtrtyugfggfffffgghhhhkjjvfffgjjvserik her tiring hhfhchgjhfrjgfghhfetugshjjgrjjgdyljgfykjffujfeujfyuttugryuhffjjgghjgfgnjfruicseikjcdeiigdetjohgerhjhfde the na ha ha ha ha ha ha ha ha ha na SA SA SA SA SA ha ha na ha hahaha ma ha ha ha ha
I hope this helps you
-7.x^3=2.7.9
x^3=-18
x=i.(3square root of 18)
Answer:
9
Step-by-step explanation:
I think the answer would be 9 but I'm not for sure
A) 4*3 x 5*2
b) 9*4 x 7*2
c) 3 x 7*4
d) 2*2 x 9*4
8*5